Media of Video for Enhancing Knowledge of Toothbrushing for Children Aged 8 – 9 in Cempaka Village - Novarita Mariana Koch; Jean Henry Raule; Rukiah Dotu (Jurnal Kesehatan Gigi, 2023)
Knowledge about health obtained in school is one of the guarantees of a healthy society. Maintaining dental hygiene through tooth brushing is among the ways improving health. Health does not only relate to the normal condition; it is a process of increasing the degree of complete health. Children and adolescents are a particular target group for health education, this is because children have much lower immunity than adults. It takes suitable media to support children's knowledge through learning. The objective of this study is to analyze the significancy of using video as media to improve knowledge of brushing teeth in children aged 8-9 years. Methods: This study used an analytic method of one group pretest-posttest design. The technique of sampling was Accidental Sampling with inclusion criteria. The amount of sample is 35 aged 8-9 years, with the total of 80 respondents. The results of the paired sample t test showed a significant difference observed from the p-value 0.00, hence Ho is rejected and Ha is accepted. The research concludes that video media affects the improved knowledge of brushing teeth.